The Effect of Er:YAG Laser Irradiation and Different Concentrations of Sodium Hypochlorite on Shear Bond Strength of Composite to Primary Teeth’s Dentin - Bahrololoomi, Zahra; Dadkhah, Azam; madsadegh Alemrajabi, Moham (Journal of Lasers in Medical Sciences, 2017)
Introduction: The aim of this study was to evaluate the effect of various concentrations of NaOCl on shear bond strength of composite resin to dentin of primary teeth, prepared with laser and bur. Methods: In this in vitro study, 48 primary molars were sectioned at mesiodistal direction and were randomly divided into 6 groups; G1: bur, G2: bur + NaOCl 2.5%, G3: bur + NaOCl 5.25%, G4: laser, G5: laser + NaOCl 2.5%, G6: laser + NaOCl 5.25%. One-Step Plus adhesive was applied after phosphoric acid gel and NaOCl over the dentin surfaces for all groups, and composite resin cylinders were bonded to the samples. After thermocycling, shear bond strengths of composite resin to dentin were measured and statistical analyses were done by means of t test and analysis of variance (ANOVA). Results: The mean shear bond strength showed no significant difference between the groups prepared with bur (13.82 ± 3.49) and laser (14.18 ± 3.65) (P > 0.05). The mean difference of shear bond strength between three groups G1, G2 and G3 and between G4, G5 and G6 were not statistically significant (P > 0.05). Scanning electron microscopy (SEM) figures showed an irregular surface in laser groups and fairly complete removal of smear layer from the orifices of the dentinal tubules, in the group in which NaOCl was used. Conclusion: The application of different concentrations of NaOCl does not significantly improve the bond strength in dentin surfaces prepared with laser or bur.